Seabird guano reshapes intertidal reef food web in an isolated oceanic islet - Andrades, Ryan; Cardozo-Ferreira, Gabriel C.; Benevides, Larissa J.; Pimentel, Caio R.; Mancini, Patrícia L.; Ferreira, Carlos E. L.; Giarrizzo, Tommaso; Joyeux, Jean-Christophe; Macieira, Raphael M. (Coral reefs, 2024)
Deposits of seabird guano on marine shores have drawn the attention of companies and naturalists for centuries. Among notable effects, allochthonous energy/matter inputs by seabirds are responsible for shifts in ecosystem functioning next to colonies. Here, we used stable isotopes of nitrogen-15 (ratios of 15 N: 14 N, expressed as δ 15 N) to trace guano incorporation in the intertidal reef community (fish and crab). The study areas were the Saint Peter and Saint Paul Archipelago (SPSPA), a remote and very small group of islets in the equatorial Atlantic Ocean, and two reference Atlantic islands where intertidal environments are not subject to the influence of guano. SPSPA intertidal reef fauna presented 3–7‰ higher δ 15 N values in comparison with local seabirds and with the intertidal reef fauna of reference islands. The intertidal food web of SPSPA appears supplemented by guano subsidies with carnivores, omnivores and herbivores 15 N-enriched in relation to a local seabird. While no difference in intertidal biota δ 15 N values was detected between references sites, 15 N-enrichement observed for SPSPA intertidal reef fauna is supported by guano subsidies. With emerged area < 0.02 km 2 , SPSPA is one of the world’s smallest archipelagos and only its main islet (Belmonte Island) has a few tidepools apt to be inhabited by fish. As guano readily drains into tidepools and reef crevices adjacent to the seabird colony, allochthonous nutrients become available and support habitat-restricted species in this small and isolated location.